Factors associated with shock in children with dengue hemorrhagic fever - Erick F Kan; T H Rampengan (Indonesian Pediatric Society, 2004)
Background Shock in dengue hemorrhagic fever (DHF) still con-stitutes an important problem in children. Predicting DHF patientswho will develop shock is difficult.Objective The aim of this study was to find out factors associatedwith shock in DHF.Methods This was a prospective observational study. Subjectswere children hospitalized from April to July 2000 who met theWHO criteria for DHF and had positive serological confirmation.Association between independent variables (age, gender, dura-tion of fever, abdominal pain, vomiting, hepatomegaly, plateletcount, hematocrit level, and nutritional status) and the dependentvariable (shock) was analyzed by logistic regression model..Results There were 85 children who met the eligibility criteriaconsisting of 50 (59%) boys and 35 (41%) girls with an averageage of 7.1 years (SD 2.88). Shock occurred in 42 (49%) children.Of the 42 children with shock, the age group of 5-9 years madeup the biggest group (57%) consisting of 23 (55%) boys and 19(45%) girls. Hepatomegaly was found in 32 (76%) children, ab-dominal pain and vomiting in 30 (71%) and 36 (86%) children,respectively, and good nutrition in 22 (52%) children. Shock oc-curred mainly on the fourth and fifth days (76%). Almost half ofthe patients (45% and 52%) had hematocrit level of 46-50% andplatelet count of 20,000-50,000/ml, respectively. By logistic re-gression analysis, it was found that duration of fever, abdominalpain, hematocrit level, and platelet count constituted indepen-dent factors correlating with shock in DHF.Conclusion Abdominal pain, fever lasting four to five days, hema-tocrit level of >46%, and platelet count of <50,000/Î¼l were associ-ated with shock in DHF